Investigation of frictional constraint effect of RBD palm stearin as lubricant by plane strain extrusion - Syahrullail, Samion (European Journals Inc., 2009)
In this paper, RBD palm stearin, which is one of the refined products of palm oil, was tested as cold metal working lubricant by plane strain extrusion. Whole experiments were carried out at room temperature 20°C. Pure aluminum A1050 was used as a workpiece. In these experiments, the extrusion loads were measured and the surface conditions of workpieces were observed. The distribution of relative velocity was calculated in the deformation zone of workpiece by applying the visioplasticity method. Similar experimental and analytical investigations were carried out for a conventional lubricant, paraffinic mineral oil, and the results were compared to those of the RBD palm stearin. Present investigation confirms that lubrication effect of RBD palm stearin reducing the frictional constraint in the cold metal forming is similar to that of mineral base lubricating oil. However, the existence of RBD palm stearin in solid state at around room temperature affects the surface condition of workpiece, and coarser roughness condition is observed in cold extrusion.